Arbasus caecus (Simon, 1911): a new member of the ancient family Buemarinoidae (Opiliones, Laniatores) and its relation to the known species - Karaman, Ivo (Biologia Serbica, 2023)
Arbasus caecus (Simon, 1911) a troglobite from caves of a region in the central Pyrenees in southern France was transferred to Buemarinoidae as the fifth species of this family. Buemarinoidae is an old phyletic lineage of Pangean origin. Fumontana deprehendor Shear, 1977, a terricole species from the Appalachian Region of eastern North America, is closely related to Arbasus caecus. Their separation occurred before Laurasia broke up into North America and Eurasia. Apart from these, two closely related troglobitic species are known from the west Mediterranean: Buemarinoa patrizii Roewer, 1956, from some caves in Sardinia and Turonychus fadriquei Derkarabetian, Prieto & Giribet, 2021, from a cave in northeastern Spain. Flavonuncia pupila Lawrence, 1959, from Madagascar is also a member of this family.